2003
DOI: 10.1002/cyto.a.10095
|View full text |Cite
|
Sign up to set email alerts
|

Development of Herceptin resistance in breast cancer cells

Abstract: Background Herceptin, a humanized antibody to HER‐2, is now utilized in the clinic for metastatic breast cancer treatment. The response rate for HER‐2+ patients is only 30% and little is known as to mechanisms of resistance. The mechanism of Herceptin action is also unknown but has been related to cell cycle inhibition. Methods The effects of Herceptin and other antibody treatments were determined by cell counting and cell cycle analysis. HER‐2 and p27 expression levels were analyzed by flow cytometry and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 14 publications
4
99
0
Order By: Relevance
“…MDA-MB-231 was included as an HER-2/neu negative tumor cell line control, and SK-BR-3 was used to represent HER-2/neu positive tumor cells. Specific lysis by Vg9 T cells was measured by standard 4-h 51 Crrelease assays. The lysis rates were obtained by the following equation: (experimental release -spontaneous release)/(maximum releasespontaneous release) 3 100.…”
Section: Cell Lines and Cytotoxicity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA-MB-231 was included as an HER-2/neu negative tumor cell line control, and SK-BR-3 was used to represent HER-2/neu positive tumor cells. Specific lysis by Vg9 T cells was measured by standard 4-h 51 Crrelease assays. The lysis rates were obtained by the following equation: (experimental release -spontaneous release)/(maximum releasespontaneous release) 3 100.…”
Section: Cell Lines and Cytotoxicity Assaysmentioning
confidence: 99%
“…The lysis rates were obtained by the following equation: (experimental release -spontaneous release)/(maximum releasespontaneous release) 3 100. Maximum and spontaneous releases were determined, respectively, by adding 0.1% Triton X-100 or complete medium to 51 Cr-labeled tumor target cells in the absence of gd T cells. Data are presented as the mean of triplicate samples.…”
Section: Cell Lines and Cytotoxicity Assaysmentioning
confidence: 99%
“…Animals were euthanized, and the tumors were removed and cut into small pieces with a sterile blade, washed twice with sterile PBS, and placed in culture dishes in medium containing F-12/ DMEM (1:1) supplemented with 20% FCS, 60 units/L insulin, and antibiotics. The medium of JIMT-1 X+ cells also contained 10 Ag/mL trastuzumab (28). After 3 days, debris and dead cells were removed, and the medium was refreshed.…”
Section: Establishment Of Sublines From Jimt-1xenograftsmentioning
confidence: 99%
“…(19,(22)(23)(24)(25) To rule out loss of epitope or epitopemasking effects, first, we validated the overexpression of HER2 receptor and function in BT-474 cells. The HER2 expression remained unaltered between the parental cells (BT-474) and the resistant cells (BT-474-R), both at the mRNA (Fig.…”
Section: Validation Of Trastuzumab-resistant Breast Cancer Cellsmentioning
confidence: 99%
“…Their results indicate that the resistant clones have not lost HER2 expression, but overexpress epidermal growth factor receptor (EGFR) and HER3. (41,42) On the other hand, Kute and colleagues (23) developed resistant cells by treating with the antibody over 2 weeks and found that PI3K and overexpression of EGFR mediate resistance. Chan and colleagues (43) cultures) and thus provide a snapshot of the evolution of TZR (Fig.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellsmentioning
confidence: 99%